Attracting FDI to the region of Lodz by its local government - Tomasz Dorożyński; Janusz Świerkocki; Wojciech Urbaniak (Comparative Economic Research. Central and Eastern Europe, 2014)
This paper evaluates the financial and non-financial incentives used by local authorities in the Province of Lodz to promote the inflow of FDI. Conclusions are based on a questionnaire study conducted in the second half of 2010 among 188 companies with foreign capital (CFC) which invested in the region, and 87 local government units hosting the majority of the CFCs included in the study. The obtained results indicate that support offered by local authorities had only a minor impact on the location decision for the investment project, and this conclusion is consistent with results of studies which assessed the role of incentives in Poland at macro, regional and sectoral levels.
Keywords: 330; FDI; incentives; Lodz Region